Determination of gold prices in Malaysia / Siti Hawa Misran - Misran, Siti Hawa (2014)
This paper aims to analyses the relationship between factors that affecting the price of gold in Malaysia. The study used Multiple Linear Regression Model to determined significant relationship between dependent and independent variables, covering data for 20 years period which are from 1993 until 2013. The researcher used four independent variables that affect the prices of gold which are crude oil price, inflation rate, exchange rate as well as gross domestic product. The empirical results have found there is positively significant relationship between crude oil price, inflation rate, exchange rate and gross domestic product. The results of the study are valuable for both academic and investor.